Teaching with Socio-Scientific Issues in Physical Science: Teacher and Students’ Experiences - Joy de la Pena Talens (Institute of Advanced Engineering and Science, 2016)
Socio-scientific issues (SSI) are recommended by many science educators worldwide for learners to acquire first hand experience to apply what they learned in class. This investigated experiences of teacher-researcher and students in using SSI in Physical Science, Second Semester, School Year 2012-2013. Latest and controversial news articles on sources of energy were chosen for analysis. Based on the findings, the teacher-researcher was able to choose issues based on a set of criteria and students related what they learned inside the classroom with real life situations and its positive and negative impact to people and environment. A model of learning approach for teaching SSI in Physical Science was proposed.